Oocyte Donation - Nalini Mahajan (European Medical Journal, 2017)
The use of donor oocytes has expanded the scope of assisted reproductive technology (ART) for women with poor oocyte quantity and quality. In vitro fertilisation with oocyte donation (IVF-OD) is considered to give better implantation, pregnancy, and livebirth rates compared to IVF with autologous oocytes. Maternal age, infertility factors, BMI, smoker status, and ethnicity reduce reproductive outcome. An increasing demand and a good success rate with oocyte vitrification programmes have led to the formation of oocyte banks, reducing the need for donor-recipient cycle synchronisation and allowing egg sharing. Obstetric and neonatal complications with donor oocytes are significantly increased in comparison to autologous IVF and spontaneous pregnancies. The risk of pregnancy-induced hypertension (PIH), pre-eclampsia (PE), prematurity, low birth weight and very low birth weight are increased, as is the need for operative delivery. The age group of these patients and the increase in obstetric and neonatal complications associated with multiple pregnancy, dictates the use of single embryo transfer. As increasingly older women enter these programmes, concerns for maternal and fetal health necessitate guidelines to set an age limit for offering the procedure. Advanced paternal age is also raising concerns in long-term follow-up studies in neonates.